(untitled) (Journal of Humanities and Social Sciences Research, 2022)
Israel’s electoral system is based on: proportional representation, meaning that the distribution of Knesset seats has 120 seats; it’s proportional to what each party receives in total votes. However, the minimum required for each party to gain representation in the Knesset is (2%) Of the total votes cast, but this percentage is usually adjusted The proportional representation system has led party leaders to control the selection of candidates for the Knesset and the ministries He placed special importance on political parties in the rise of young leaders to senior positions, equating with popular and mass support That those leaders have made elections an expression of the interaction of forces within society. Israel introduced the principle of proportional representation in order to represent as many multicultural communities as possible Elections to the Knesset are held every four years, and the Knesset can decide to hold early elections under certain circumstances Israel’s electoral system also has its own nature; distinguishing it from other international electoral systems. The electoral system has undergone many changes and innovations aimed at creating an environment of governmental stability in Israel. Israel’s electoral system has characteristics and features defined by the Second Electoral Law (1951) and the Basic Law on Elections (1958) relating to elections The legislative function is to be elected by equal, secret and proportional universal suffrage.